Shame revealed. Gloss to the discussion about the Catholic Church (and not only) = Wstyd ujawniany. Glosa do dyskusji o Kościele katolickim (i nie tylko) - Drozdowicz, Zbigniew (Przegla̜d religioznawczy, 2018)
In these considerations he recalls the statements of those who reveal the occurrence of such embarrassing phenomena as pedophilia or sexual harassment in the Catholic Church. The problem, however, is not only about their occurrence in it, but also about their concealment by those who recognize that making them public can harm more than help this Church. Just like the authors of publications on these negative phenomena, which I cite, I do not share this position.